A Review of Therapeutic Agents Given by Convection-Enhanced Delivery for Adult Glioblastoma - Nathaniel W. Rolfe; Nicholas B. Dadario; Peter Canoll; Jeffrey N. Bruce (MDPI AG, 2024)
Glioblastoma remains a devastating disease with a bleak prognosis despite continued research and numerous clinical trials. Convection-enhanced delivery offers researchers and clinicians a platform to bypass the blood-brain barrier and administer drugs directly to the brain parenchyma. While not without significant technological challenges, convection-enhanced delivery theoretically allows for a wide range of therapeutic agents to be delivered to the tumoral space while preventing systemic toxicities. This article provides a comprehensive review of the antitumor agents studied in clinical trials of convection-enhanced delivery to treat adult high-grade gliomas. Agents are grouped by classes, and preclinical evidence for these agents is summarized, as is a brief description of their mechanism of action. The strengths and weaknesses of each clinical trial are also outlined. By doing so, the difficulty of untangling the efficacy of a drug from the technological challenges of convection-enhanced delivery is highlighted. Finally, this article provides a focused review of some therapeutics that might stand to benefit from future clinical trials for glioblastoma using convection-enhanced delivery.